1998
DOI: 10.1038/bjc.1998.583
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome alterations in breast carcinomas: frequent involvement of DNA losses including chromosomes 4q and 21q

Abstract: Summary Comparative genomic hybridization was applied to map DNA gains and losses in 39 invasive ductal breast carcinomas. Frequent abnormalities included gains on chromosomal regions lq, 8q, 11q12-13, 16p, 19, 20q and X as well as frequent losses on 1 p, 5q, 6q, 9p, llq, 13q and 16q. Furthermore, frequent losses on 4q (20 cases) and 21q (14 cases) were found for the first time in this tumour type. High copy number amplifications were observed at 8q12-24, 11qll-13 and 20q13-ter. Highly differentiated tumours w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
33
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 35 publications
6
33
0
Order By: Relevance
“…None of the alterations identified in myoepithelial carcinomas are unique, and they have been previously described in invasive breast carcinomas with luminal phenotype (Buerger et al, 1999;Nishizaki et al, 1997;Roylance et al, 1999;Schwendel et al, 1998;Tirkkonen et al, 1998). The most common alterations identified in myoepithelial carcinoma (loss of 16q and 17p) are also regions commonly deleted in ductal carcinomas of no special type.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…None of the alterations identified in myoepithelial carcinomas are unique, and they have been previously described in invasive breast carcinomas with luminal phenotype (Buerger et al, 1999;Nishizaki et al, 1997;Roylance et al, 1999;Schwendel et al, 1998;Tirkkonen et al, 1998). The most common alterations identified in myoepithelial carcinoma (loss of 16q and 17p) are also regions commonly deleted in ductal carcinomas of no special type.…”
Section: Discussionmentioning
confidence: 87%
“…The most striking observation from this study is the paucity of alterations identified in myoepithelial carcinomas (mean 2.1) compared with "ordinary" breast carcinomas having luminal differentiation. The mean number of alterations reported in the literature in Grade I invasive ductal carcinomas of no special type is 5.4 (range of means is 3.6 -8.0), and 11.7 in Grade III tumors (range of means 8.4 -13.8) (Buerger et al, 1999;Nishizaki et al, 1997;Roylance et al, 1999;Schwendel et al, 1998;Tirkkonen et al, 1998). The data in myoepithelial tumors are surprising in view of their aggressive morphology and behavior.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…DcR3 coding gene was located at human chromosome 20q13.3, which is also a site prone to gene amplification and rearrangement (Schwendel et al, 1998). However, whether the overexpression of DcR3 in tumor tissues is dependent on gene amplification is still ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…This gene maps to chromosome 4q25-q26. This region is commonly deleted in human breast cancer (Tirkkonen et al, 1997;Schwendel et al, 1998), ovarian cancer (Sonoda et al, 1997), lung cancer (Shivapurkar et al, 1999), hepatoma (Chou et al, 1998;Piao et al, 1998), cervical cancer (Mitra et al, 1994), head and neck squamous cell carcinoma (Pershouse et al, 1997), colon cancer (Arribas et al, 1999), and oral cancer (Wang et al, 1999). A candidate for the iris hypoplasia locus also maps on 4q25 (Heon et al, 1995).…”
Section: Discussionmentioning
confidence: 99%